A Case of Tumid Lupus Erythematosus Successfully Treated with Topical Tacrolimus and Hydrocortisone 17-Butyrate - Funda Tamer; İrem Özdemir; Betül Öğüt; Özlem Erdem (Gazi Medical Journal)
Tumid lupus erythematosus is an uncommon subtype of chronic cutaneous lupus erythematosus. Hereby, we report a 36-year-old male patient with tumid lupus erythematosus who presented with erythematous papules and plaques on the face and neck who showed significant improvement after treatment with topical tacrolimus and topical hydrocortisone 17-butyrate.